Construction of highly enantioselective spiro-oxindole derivatives with fused chromene via organocascade catalysis. Issue 57 (31st May 2016) - Kumari, Prathibha; Nandi, Sekhar; Kumar, Gaurav; Khan, Noorul H.; Kureshy, Rukhsana I.; Abdi, Sayed H. R.; Suresh, E.; Bajaj, Hari C.
Abstract : A first highly enantioselective addition of naphthols and sesamol to indolylidene cyanoacetate derived from isatins was carried out in the presence of bi-functional quinine thiourea as organocatalyst. Abstract : A first highly enantioselective addition of naphthols and sesamol to indolylidene cyanoacetate derived from isatins was carried out in the presence of bi-functional quinine thiourea as organocatalyst. Under optimized reaction conditions the present catalytic system gave spiro-oxindole derivatives with excellent yield and enantioselectivity (up to 99%) at very low catalyst loading (2 mol%). The absolute configuration of3i was determined by single X-ray crystallographic analysis to be the S isomer of the product. A catalytic cycle is proposed based on NMR, IR and kinetic studies.